(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: In the field of orthopaedics, the use of additive manufacturing (AM) has significantly risen. The applications of AM include the creation of anatomical models, the design of surgical instruments and tools, splints, implants, and prostheses. A quick assessment of several research articles reveals that patient-specific orthopaedic procedures have a wide range of applications and point the way for new paths in the field. This study aims to determine the optimal applications for additive manufacturing in the field of orthopaedics. It also describes how to prepare a 3D printed model utilising this technology and provides information on orthopaedic applications. In the field of orthopaedics, AM offers a versatile solution that enables the replacement of standard goods with customised ones and allows for the formation of specialised implants in the desired shape and size. With the aid of this technology, a 3D model of the patient’s anatomy is built, which is utilised to do mock operations and is beneficial for extremely difficult surgical diseases. It raises the success rate of the procedure and makes the surgeon’s job more accessible. A precise fit implant for the individual patient is made possible by AM’s limitless geometric freedom. The condition of bone deformities is captured using a variety of scanning methods, and the model is printed with their assistance. It provides accurate physical model generation that is also beneficial for medical education, surgical planning, and training. As each patient’s data is unique, this technology can assist in resolving current issues